Impact of Manpower Planning and Mutation on Employee Performance: BPJS Employment South Sumatra and Bangka Belitung - Dwi Astuti; Zunaidah Zunaidah; Muhammad Ichsan Hadjri; Marlina Widiyanti (Journal of Management, Economic, and Financial, 2024)
The performance of employees at BPJS Employment, a state institution in Indonesia responsible for labor social security, has faced significant challenges and fluctuations. Particularly, the Regional Office of South Sumatra and Bangka Belitung experienced notable performance changes due to various internal policies. This study aims to investigate the impact of manpower planning and mutation on employee performance at BPJS Employment Regional Office South Sumatra and Bangka Belitung. The research examines how effective human resource planning and employee rotations influence performance outcomes. The study encompasses a population of 337 employees, with a sample of 183 respondents selected through a simple random sampling technique using the Slovin formula with a 5% error margin. Multiple linear regression analysis reveals that both manpower planning and mutations positively and significantly affect employee performance. The findings suggest that better manpower planning enables management to recruit the right number of employees, ensuring they are appropriately placed in positions that match their skills and organizational needs. Additionally, the mutation process, when aligned with job requirements and employee achievements, can enhance overall performance. These results highlight the necessity for BPJS Employment to continuously evaluate and improve their HR planning and mutation strategies to achieve optimal employee performance.